A convolutional neural network for fast upsampling of undersampled tomograms in X‐ray CT time‐series using a representative highly sampled tomogram. (23rd April 2019) - Bellos, Dimitrios; Basham, Mark; Pridmore, Tony; French, Andrew P.
Abstract : A convolutional neural network has been designed to quickly and accurately upscale the sinograms of X‐ray tomograms captured with a low number of projections, effectively increasing the number of projections. This is particularly useful for tomograms that are part of a time‐series as, in order to capture fast‐occurring temporal events, tomograms have to be collected quickly, requiring a low number of projections. The upscaling process is facilitated using a single tomogram with a high number of projections for training, which is usually captured at the end or the beginning of the time‐series when capturing the tomogram quickly is no longer needed. Abstract : X‐ray computed tomography and, specifically, time‐resolved volumetric tomography data collections (4D datasets) routinely produce terabytes of data, which need to be effectively processed after capture. This is often complicated due to the high rate of data collection required to capture at sufficient time‐resolution events of interest in a time‐series, compelling the researchers to perform data collection with a low number of projections for each tomogram in order to achieve the desired `frame rate'. It is common practice to collect a representative tomogram with many projections, after or before the time‐critical portion of the experiment without detrimentally affecting the time‐series to aid the analysis process. For this paper these highly sampled data are used to aid feature detection in the rapidly collected tomograms by assisting with the upsampling of their projections, which is equivalent to upscaling the gθ‐axis of the sinograms. In this paper, a super‐resolution approach is proposed based on deep learning (termed an upscaling Deep Neural Network, or UDNN) that aims to upscale the sinogram space of individual tomograms in a 4D dataset of a sample. This is done using learned behaviour from a dataset containing a high number of projections, taken of the same sample and occurring at the beginning or the end of the data collection. The prior provided by the highly sampled tomogram allows the application of an upscaling process with better accuracy than existing interpolation techniques. This upscaling process subsequently permits an increase in the quality of the tomogram's reconstruction, especially in situations that require capture of only a limited number of projections, as is the case in high‐frequency time‐series capture. The increase in quality can prove very helpful for researchers, as downstream it enables easier segmentation of the tomograms in areas of interest, for example. The method itself comprises a convolutional neural network which through training learns an end‐to‐end mapping between sinograms with a low and a high number of projections. Since datasets can differ greatly between experiments, this approach specifically develops a lightweight network that can easily and quickly be retrained for different types of samples. As part of the evaluation of our technique, results with different hyperparameter settings are presented, and the method has been tested on both synthetic and real‐world data. In addition, accompanying real‐world experimental datasets have been released in the form of two 80 GB tomograms depicting a metallic pin that undergoes corruption from a droplet of salt water. Also a new engineering‐based phantom dataset has been produced and released, inspired by the experimental datasets.